Recuperação de mata ciliar da Bacia do Rio Doce atingida pelo rejeito de fundão (Mariana, MG): remediação de éter amina e sódio - Alessandra Rondina Fontanesi Gomes (2023)
In November 2015, the breach of the Fundão Dam in Mariana, Minas Gerais, Brazil, operated by the mining company Samarco, spread approximately 55 million cubic meters of iron ore processing waste throughout the Rio Doce Basin. In the beneficiation process, the ore is treated with ether-amine and sodium. The presence of these substances in the waste was confirmed in affected areas, with high levels of sodium (average of 70 mg/kg) and ether amine (10-20 mg/kg), associated with an elevated pH (> 8.0). Ether amine in the soil is degraded into ammonia/ammonium ions under low pH conditions. These ions, at high concentrations, are toxic to native and sensitive agronomic plants, causing various symptoms of toxicity, growth suppression, decline in sensitive crops, and plant death. Excess N-ammoniacal derived from the dissociation of ether amine primarily causes symptoms of toxicity such as hypergrowth. Excess sodium in the soil affects properties such as cation exchange, permeability, and aggregation, in addition to causing water stress. This study aims to evaluate the establishment of a planted forest in an area affected by the waste under different remediation strategies. It also aims to select physical-chemical, biological, and phytoremediation procedures, including the identification of tree species suitable for the recovery of impacted riparian forests. The study areas include an undisturbed riparian forest area not affected by the waste, a degraded area affected by the waste without planting, and an experimental area affected by the waste from the Fundão Dam. In the experimental area, four treatments were implemented: T1 - Physical remediation (15 cm in the surface layer) + Organic Matter (OM) before transplantation + double inoculation; T2: Intact sediment + OM before transplantation + double inoculation; T3: Physical remediation (15 cm in the surface layer) + OM before transplantation; T4: Intact sediment + OM before transplantation. The results, 12 and 24 months post-planting, demonstrate that tolerant species showed hypergrowth due to the phytoremediation of excess ammonia in the soil, with a 100% growth increase after 1 year of cultivation. This resulted in a reduction of ether amine concentration in the experimental area compared to the degraded area. The treatment with all four remediation strategies implemented proved to be the most effective in reducing ether amine and sodium, promoting plant growth, and restoring soil quality and fertility.